An objective method of locating optimum pitch - NP, Nataraja (Journal of All India Institute of Speech and Hearing)
A review of literature, on the methods of locating optimum pitch which is an important step in most of the voice therapies, shows that all of them are subjective and differ from each other. The present study attempted to locate the optimum pitch, objectively, using the resonance of vocal tract, which is a common factor in all the present definitions of optimum pitch. Experiments were conducted to find out the natural frequency of vocal tract, using an external sound source, in the frequency range of 80 Hz-300 Hz and 750 Hz—1050 Hz. It was possible to determine the natural frequency of vocal tract, only by using the frequency range of 750 Hz—1050 Hz. It was also found there was a consistent and constant relationship between the fundamental frequency of voice and the natural frequency of vocal tract in case of superior male speakers age ranging 20-25 years who were, presumably, using their optimum pitch. The relationship was 1:8. Using this relationship it was possible to predict either the fundamental frequency of voice or the natural frequency of vocal tract in case of other superior male speakers, when one of these frequencies were known. Thus this method was used to locate optimum pitch in dysphonics